The role of mathematics education students in motivating learners to use three-dimensional geometry learning media - Tali Wangge, Maria Carmelita; Lewa, Yusta Selvianjeli; Tawa, Maria Goreti; Jodo, Dominikus Kaka; Pantaleon, Kristianus Viktor; Hari, Christina Lusiana (Universitas Islam Negeri Raden Intan Lampung, 2025)
Mathematics learning, particularly three-dimensional geometry, is often perceived by junior secondary school students as abstract and difficult, which can negatively affect learning motivation and engagement. Instructional innovation is therefore required to support students’ understanding and participation. This study aims to systematically review the literature on the role of university students in motivating learners to use three-dimensional geometry learning media in mathematics education. A qualitative systematic literature review (SLR) design was employed, analyzing scholarly articles, books, and conference proceedings published between 2010 and 2025. Data were examined using thematic content analysis to synthesize patterns related to learning media, student motivation, and the pedagogical involvement of university students. The findings indicate that three-dimensional geometry learning media, including concrete manipulatives and technology-based tools, consistently enhance students’ motivation, engagement, and conceptual understanding. In addition, the involvement of university students as facilitators and learning companions strengthens the effectiveness of media use by creating more interactive and supportive learning environments. The review also reveals that contextual factors such as instructional strategies, media design, and infrastructure influence learning outcomes. Overall, this study highlights that combining geometry learning media with university student involvement represents a strategic pedagogical approach to support more meaningful and student-centered mathematics learning.